2009
DOI: 10.1016/j.jacc.2008.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Infusion of Eptifibatide After Successful Coronary Intervention

Abstract: After uncomplicated PCI, eptifibatide infusion can be abbreviated safely to <2 h. It is not inferior to the standard 18-h infusion in preventing ischemic outcome, and it may be associated with less major bleeding. (Brief Infusion of Eptifibatide Following Percutaneous Coronary Intervention [BRIEF PCI]; NCT00111566).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 35 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…A GPI bolus or 2‐hour infusion with clopidogrel, as compared with a GPI infusion for 12 to 18 hours, decreased bleeding complications with no difference in outcomes 7, 8. Furthermore, Gurm et al20 analyzed 21 296 patients; of these, 4511 were treated with eptifibatide bolus at the time of PCI and 16 785 received standard therapy (bolus plus infusion).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A GPI bolus or 2‐hour infusion with clopidogrel, as compared with a GPI infusion for 12 to 18 hours, decreased bleeding complications with no difference in outcomes 7, 8. Furthermore, Gurm et al20 analyzed 21 296 patients; of these, 4511 were treated with eptifibatide bolus at the time of PCI and 16 785 received standard therapy (bolus plus infusion).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, future studies are needed to compare the PD effect of ticagrelor and eptifibatide bolus with ticagrelor and unfractionated heparin/bivalirudin. Third, because clopidogrel and eptifibatide 18‐ versus 2‐hour infusion increased bleeding,8 we did not randomize patients to ticagrelor and eptifibatide 18‐ versus 2‐hour infusion. Fourth, because it has been demonstrated23 that the vasodilator‐stimulated phosphoprotein assay had minor differences as compared with the LTA measurements, we did not perform the vasodilator‐stimulated phosphoprotein assay to measure platelet reactivity index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate PI to either clopidogrel or ticlopidine at steady state was common, but nonresponse to both drugs was infrequent (3.5%), suggesting that inadequate PI is drug specific rather than class specific. Angiolillo et al (135) (137). The primary end point, incidence of ischemic injury, was 30.1% in the short group and 28.3% in the standard group.…”
Section: Pharmacotherapymentioning
confidence: 96%
“…[5][6][7] It is unclear, however, as to how long platelet inhibition must be maintained after contemporary PCI, and a small randomized study previously suggested that an eptifibatide bolus and a short infusion (<2 hours) were noninferior to the standard regimen of bolus plus infusion and might be associated with a reduction in bleeding. 8 …”
mentioning
confidence: 99%